Developing Grade 5 Students’ Scientific Habits of Mind Through Community-based Science Learning - Phoopanna, Ariya; Nuangchalerm, Prasart (Department of Science Education, Universitas Sultan Ageng Tirtayasa, 2022)
Students are future citizens who will be able to make more informed decisions on social movements. Reasoning, inherent skepticism, the ability to situate things in bigger settings and discern connections are all part of scientific habits of mind. This action research aimed to develop grade 5 students’ scientific habits of mind through community-based science learning to meet the requirement of passing criteria 70% of mean score. Target group were 12 of grade 5 students from one primary school, located in Mahasarakham province, Thailand. The research tools were 2 spirals of lesson plan and community-based science learning organization, observational tools were 2 sets of 30-multiple choice test of scientific habits of mind, 10 items of 5-rating scale of scientific habits of mind questionnaire, and students’ interview form towards community-based learning. Mean, standard deviation, and percentage were employed for data analysis. The findings pointed that first spiral of learning organization, students had 82.92% of mean score. The second spiral of learning organization, students had 90.83% of mean score. It can be concluded that community-based learning help students to gain their scientific habits of mind.